Tubulocystic renal cell carcinoma: is there a rational reason for targeted therapy using angiogenic inhibition? Analysis of seven cases - Steiner, Petr; Hora, Milan; Stehlik, Jan; Martinek, Petr; Vanecek, Tomas; Petersson, Fredrik; Michal, Michal; Korabecna, Marie; Travnicek, Ivan; Hes, Ondrej (Virchows Archiv, 2013)
Generally, patients with renal cell carcinoma (RCC) are viewed as potential candidates for antiangiogenic targeted therapy. Tubulocystic RCC (TCRC) is a recently described entity which may behave aggressively, and the rationale for antiangiogenic therapy in this group of renal tumors has yet to be determined. Seven TCRCs and five non-tumor tissue samples from seven patients were subjected to relative expression analysis of mRNA levels of 16 genes involved in three angiogenic signal pathways: (1) VHL/HIF, (2) RTK/mitogen-activated protein kinase (MAPK), and (3) PI3K/Akt/mTOR. Two of them, pathways (2) and (3), are often targeted by antiangiogenic agents. We also determined the mutation and methylation status of the VHL gene. Finally, the levels of vascular endothelial growth factor A (VEGFA), HIF-1α, HIF-2α proteins, and phosphorylated mTOR protein were also determined. The comparison of tumor and control samples revealed no changes of mRNA levels of the following genes: VHL, HIF-1α, HIF-2α, PTEN, Akt2, Akt3, mTOR, VEGFA, KDR, HRas, C-Jun, EGFR, and FGF2. Significantly elevated mRNA level of TP53 was found, while the mRNA levels of FLT1 and C-FOS were reduced in tumor samples. No mutations or methylation in the VHL gene were found. Changes in levels of studied proteins VEGFA, HIF-1α, HIF-2α, and increased phosphorylation of mTOR protein were not found. Three studied angiogenic pathways (VHL/HIF, RTK/MAPK, and PI3K/Akt/mTOR) seem not to be upregulated in TCRC samples, so there appears to be no rationale for a general recommendation of antiangiogenic targeted therapeutic protocols for patients with these tumors.
Keywords: nádory ledvin; Vascular Endothelial Growth Factor A; TOR Serine-Threonine Kinases; signální transdukce; Phosphorylation; Signal Transduction; inhibitory angiogeneze; Humans; lidé středního věku; fosforylace; Von Hippel-Lindau Tumor Suppressor Protein; Molecular Targeted Therapy; TOR serin-threoninkinasy; Female; Aged; dospělí; výsledek terapie; senioři; lidé; Hypoxia-Inducible Factor 1, alpha Subunit; Neovascularization, Pathologic; Adult; faktor 1 indukovatelný hypoxií - podjednotka alfa; ženské pohlaví; Male; vaskulární endoteliální růstový faktor A; Middle Aged; Treatment Outcome; Angiogenesis Inhibitors; cílená molekulární terapie; karcinom z renálních buněk; transkripční faktory bHLH; Carcinoma, Renal Cell; mužské pohlaví; nádorový supresorový protein VHL; Kidney Neoplasms; patologická angiogeneze; Basic Helix-Loop-Helix Transcription Factors